118 Contribution of sperm methylome to bull fertility and interactions with DNA polymorphism. (7th December 2018) - Kiefer, H; Perrier, J; Sellem, E; Prézelin, A; Gasselin, M; Jouneau, L; Piumi, F; Al Adhami, H; Weber, M; Fritz, S; Boichard, D; Le Danvic, C; et al.
Abstract: Spermatozoa have a remarkable epigenome in line with their degree of specialization, their unique nature and different requirements for successful fertilization. While bull semen is widely used in artificial insemination, the literature describing DNA methylation in bovine spermatozoa is still scarce. In the context of genomic selection, more information on the epigenetic features transferred to the embryo alongside the paternal genetic heritage is necessary, in order to improve semen quality control procedures and bull fertility. We characterized the bull sperm methylome relative to bovine fibroblasts and monocytes using reduced restriction bisulfite sequencing (RRBS). A wide majority of differentially methylated cytosines (DMCs) were less methylated in sperm than in somatic cells. Consistent with previous studies in other species, these hypomethylated DMCs were enriched for genes relevant to the germline differentiation program and sperm functions. The most remarkable observation was a dramatic enrichment for repeats and particularly for satellites, which may partly account for the lower global methylation we observed in bull sperm relative to sperm from other species (LUminometric Methylation Assay). We next investigated whether fertility biomarkers could be identified in the sperm methylome. Based on field fertility indicators, we compared fertile ejaculates, subfertile ejaculates and ejaculates from bulls with a disappointing career in contradiction with genomic predictions (Montbéliarde breed, n=10/group). The median age at production was consistent among groups and the phenotypic characterization revealed no significant differences except for the proportion of motile sperm, which was reduced in disappointing bulls. We identified 4823 DMCs targeting genes involved in signaling pathways, angiogenesis and the response to growth factors. Since DNA methylation is affected by the CpG content of the genome and its alteration by DNA polymorphism, an integrative approach was conducted to identify CpGs and SNPs in correlation, which revealed both direct and indirect interactions between the genome and the epigenome.